Quantitative Analysis Of FË‰ Ion Recognition By A New Chemosensor from Flavon Group - R Rahmawati; Syarifa Wahidah Al-Idrus; Baiq Nila Sari; Bambang Purwono; Sabirin Matsjeh (Chemistry Education Program, the University of Mataram, 2020)
A new chemosensor S8 compound from the flavon group that has been successfully synthesized. Test its ability as a chemosensor for F- anion, providing positive results that it can recognize F- anion with response to an increase in fluorescent solution. Titration of S8 solution in DMSO solvents was carried out with F- anion at various concentrations and then measurements were made on fluorometry instruments. The fluorescent titration emission spectrum shows that the S8-FË‰ host-guest interaction quantitatively in the form of LOD and kass. LOD and Kass values are 6.43 Ã— 10Ë‰4 M and 2 Ã— 106 MË‰1, respectively.